Rumah Gadang 21 Ruang Nagari Abai Kabupaten Solok Selatan Sumatera Barat - Tuti, Utari; Retnaningtiyas, Susanti (Al-DYAS, 2024)
Cultural education is one thing that is very important to learn and understand, besides that culture cannot be separated from everyday life. Education is a basic need for every individual in society, while culture is a complete and comprehensive unity that applies in society, values and the idea can of course be internalized by a group of people in a living environment within a certain period of time (Ratna, 2005). Traditional houses in the West Sumatra region have various kinds of unique characteristics in facing the development of the times since they were founded. At that time, architecture had proven that the application of science had a very far-sighted outlook with the survival of these traditional buildings to this day. Rumah Gadang is widely spread throughout West Sumatra Province and has various sizes and shapes. One of the areas that has a unique Rumah Gadang shape is Nagari Abai, Sangir Batang Hari District, South Solok Regency which has lots of Rumah Gadang with a unique long shape. The meaning of the Rumah Gadang building also has a different meaning in every corner of the building.